Superoxide dismutase isoenzymes of the synovial fluid in rheumatoid arthritis and in reactive arthritides. - Marklund, S L (1986)
The activity of superoxide dismutase isoenzymes was determined in knee joint synovial fluid from 21 patients with rheumatoid arthritis, nine patients with reactive arthritides, and from 17 patients before arthroscopy or arthrotomy for suspected meniscal or ligament injury (controls). Extracellular superoxide dismutase was the major isoenzyme and accounted for about 80% of the total superoxide dismutase activity in the controls. The pattern of the superoxide dismutase isoenzymes was significantly different in rheumatoid arthritis, extracellular (EC) superoxide dismutase being half, CuZn superoxide dismutase double, and the total superoxide dismutase activity a third lower than the activity in the synovial fluid of the controls. The superoxide dismutase activities were similar in synovial fluid from the controls and from the patients with reactive arthritides. The total superoxide dismutase activity was almost three times higher in control synovial fluid than in normal human plasma, but 300 times lower than in human tissues.